2017
DOI: 10.3892/ol.2017.7196
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical implications of TERT promoter mutation in glioblastoma multiforme

Abstract: Abstract. The promoter region of the telomerase reverse transcriptase gene (TERT) is mutated in a subpopulation of patients with glioblastoma multiforme (GBM). In the present study, preclinical and clinical implications of the mutation were analyzed in 25 GBMs to evaluate its utility as a therapeutic target. Associations between the TERT promoter mutation and a number of preclinical/clinical characteristics were analyzed. Notably, the TERT promoter mutation was identified in 92.3% of GBMs where dissociated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…For example, a negative relationship was observed between telomerase activity and clinical outcome in breast cancer, colorectal cancer and gastrointestinal stromal tumors [ 38 , 40 , 41 ]. In gliomas, TERT promoter mutations lead to higher telomerase activity [ 42 ] but the associations between TERT promoter mutations and clinical outcomes are still controversial [ 43 , 44 ]. In the Short TL group, more cancer types also showed significantly different survival probabilities ( Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a negative relationship was observed between telomerase activity and clinical outcome in breast cancer, colorectal cancer and gastrointestinal stromal tumors [ 38 , 40 , 41 ]. In gliomas, TERT promoter mutations lead to higher telomerase activity [ 42 ] but the associations between TERT promoter mutations and clinical outcomes are still controversial [ 43 , 44 ]. In the Short TL group, more cancer types also showed significantly different survival probabilities ( Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…TERT promoter muts attract transcriptional factors that should not normally act at this site and thus contribute to the activation of TERT expression [26]. TERT muts have originally been associated with tumors of low self-renewal [19] including GBMs; in the latter, TERT muts increase the capacity of self-renewal and thus survival and growth [28], despite the fact that they do not contribute to increased size of the telomeres [26]. Previously, TERT promoter muts were shown to interact with IDH muts conferring a dual prognostic impact [11,29].…”
Section: Discussionmentioning
confidence: 99%
“…5 In vitro studies have demonstrated a strong association between the presence of TERT mutations and sphere-forming capacity of GBM cells. 21 An extensive network of transcription factors has been demonstrated to be involved in TERT regulation, with increasing evidence of TERT involvement in the regulation of downstream cellular processes such as cellular signaling and cell cycle regulation. 6 In squamous cell carcinoma, TERT downregulation was shown to result in decreased expression of matrix metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…TERT promoter mutations occur commonly in primary GBM and are associated with worse prognosis . In vitro studies have demonstrated a strong association between the presence of TERT mutations and sphere‐forming capacity of GBM cells . An extensive network of transcription factors has been demonstrated to be involved in TERT regulation, with increasing evidence of TERT involvement in the regulation of downstream cellular processes such as cellular signaling and cell cycle regulation .…”
Section: Discussionmentioning
confidence: 99%